Uma abordagem analítica do legato através de parâmetros acústicos e cinemáticos na performance de clarinetistas - Alexandre Pereira da Silva (2022)
The study aimed to relate aspects of clarinetists’ finger movements to acoustic characteristics, specifically to the quality of legato; for this purpose, three databases were used: (1) the information collected on the kinematic characteristics of the musicians’ fingers, namely speed and acceleration; (2) the information calculated by selected acoustic descriptors to extract quantitative data on specific musical intervals, and (3) the opinions of forty listeners, among professional and student clarinetists, on the quality of legato in some previously selected intervals. The results indicate that kinematic aspects of the fingers can affect the quality of legato, and apparently, it is easier to connect an ascending interval than a descending interval, even when dealing with a relatively short minor third interval. Furthermore, the study found that if the fingers move excessively fast, the legato can be impaired, even if there is perfect synchronization between the speed peaks in the descending transitions.